Livestock in rural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Strategy for sustainable livestock production in the tropics by Thomas Preston and Enrique Murgueitio 1992 89pp ISBN 958 95215 0 2 Pbk CIPAV AA20591 Cali COLOMBIA